Attitude Control of Flexible System by Shaping Constant-Amplitude Input - Ibrahim, Idris; Parman, Setyamartana; Zainuddin, Azman (2008)
Attitude manoeuvres of satellites in space are generally performed by using thrusters. Thrusts resulted usually can not be variable, they are constant in amplitudes. When a satellite has flexibility in its structural members or in its member’s joints, under constant-amplitude thrust, large structural vibration and attitude angle oscillation may occur during and after the manoeuvre. This attitude oscillation of course will disturb its pointing to earth. So, this oscillation should be removed or should be reduced to the small value under the maximum permissible pointing errors. To reduce residual attitude angle oscillations, input shaping method is used in this paper. This method determines number and time locations of input pulses to be used to the satellite regarding to the system’s flexibility. As the result, the input consists of a sequence of constant pulses in the suitable directions and time switching locations. The satellite studied in this paper consists of a main body and two solar panels. The main body is a cubic rigid box, while the solar panels are large in size and they are supposed to be flexible. Finite element method is used to discrete the solar panel’s motion. The solar panels are modelled as a collection of rectangular bending plate elements. Then, attitude manoeuvres of the satellite are simulated numerically. By shaping the inputs, the residual oscillation of attitude angles of the satellite can be suppressed successfully into an expected level.